The artist in society : talking with Hershell West - Ma, Eve A. (PalominoPro, 2017)
Hershell West - painter, muralist, art advocate, art teacher - was born and raised in Enterprise, Alabama. A black man in the segregated south, neither his family nor his society expected him to become an artist but he surmounted the odds, obtained first a BA and then a MFA from the University of South Florida. After working for a while in Florida, he moved to the San Francisco Bay Area where he continues to live. West has executed commissions for murals in both Florida and California. In addition, his paintings have been exhibited in many venues. He has worked as chief, and often only, assistant to muralist John Wehrle. He has been board chair of the Richmond Art Center, of ProArts of Oakland, of MAW (Media Art Works) and has sat on, and chaired the Arts & Culture Commissions of both Alameda County and the City of Richmond in the San Francisco Bay Area. And he has taught - especially at-risk youth - both in a youth authority setting and through the Richmond Art Center. In a word, he exemplifies the positive contributions that many artists make to our society, creating works of beauty and at the same time, using art to help those around them. --